HIV-AIDS AND ISLAM’ IN INDONESIA; POWER NARRATIVES AND RESISTANCE - Syamsu Madyan (Jurnal Ijtihad, 2019)
This paper can be identified as an AIDS anti-stigma related project, which orients its query to the particular problem of  social  stigma based on religion in Indonesia. It analyze how Islamic authorities and leadership in Indonesia has the  power in the construction of  AIDS realities as the reproduction  of  AIDS  discourses  in  Indonesia  generates  the  stigma towards Muslims living with the infection. This paper will be demonstrating the scenario of power, exclusion and resistance within the context of that stigma.Keywords: AIDS, religion, resistence